Dual Burdens of Care: "Sandwiched Couples" in East Asia. (December 2018) - Tan, Poh Lin
Objective: To estimate proportions of married couples aged 30 to 59 years who face simultaneous demands from elderly parents and children in China, Japan, Korea, and Taiwan, and the effects on couples' life and marital satisfaction.Method: Using data from the 2006 East Asian Social Survey, proportions of sandwiched couples were estimated using three definitions: co-residence, co-residence or nearby residence, and co-residence or frequent provision of financial/physical assistance. Logistic regression models were used to assess the effects on life and marital satisfaction.Results: Three-generational co-residence is more common in Taiwan and Japan (24.3% and 21.4%), whereas co-residence or provision for both generations is higher in Taiwan and Korea (53.7% and 44.5%). The strain of being sandwiched is associated with lower life and marital satisfaction only among women.Discussion: Intergenerational transfers of care play a major role in elderly support in East Asia but take a toll on the well-being of married women.